A Metaphoric Mind: Selected Writings of Joseph Couture - edited by Ruth Couture and Virginia McGowan (Athabasca University Press, 2013)
Dr. Joseph Couture (1930Ð2007), known affectionately as "Dr. Joe," stood at the centre of some of the greatest political, social, and intellectual struggles of Aboriginal peoples in contemporary Canada. A profound thinker and writer, as well as a gifted orator, he easily walked two paths, as a respected Elder and traditional healer and as an educational psychologist, one of the first Aboriginal people in Canada to receive a PhD. His work challenged and transformed long-held views of Canada's Indigenous peoples, and his vision and leadership gave direction to many of the current fields of Aboriginal scholarship. His influence extended into numerous areasÑeducation, addictions and mental health treatment, community development, restorative justice, and federal correctional programming for Aboriginal peoples. With a foreword by Lewis Cardinal, A Metaphoric Mind brings together for the first time key works selected from among Dr. Joe's writings, published and unpublished. Spanning nearly thirty years, the essays invite us to share in his transformative legacy through a series of encounters, with Aboriginal spirituality and ancestral ways of knowing, with Elders and their teachings, with education and its role in politicization, self-determination, and social change, and with the restorative process and the meaning of Native healing.